Kajian Elemen Perancangan Kota pada Koridor Jalan T.B. Simatupang-Jalan Pinang Baris-Simpang Kampung Lalang di Kecamatan Medan Sunggal, Medan - Sagala, Peranita; Wisdianti, Dara; Novalinda, Novalinda (PT. Arsil Reka Engineering, 2025)
The development of urban areas is essentially the result of a dynamic interaction between regulations and the growth of the community. One such regulatory instrument is the Building and Environmental Layout Plan (RTBL). The RTBL serves as a guide and control mechanism for development, ensuring that the arrangement of buildings and the environment in selected areas meets criteria for sustainable planning. The T.B. Simatupang–Pinang Baris–Kampung Lalang Intersection corridor in the Medan Sunggal District is a secondary arterial road in Medan City that plays a crucial role in balancing the city's overall growth. Identifying urban design elements is essential to creating an urban plan that reinforces Medan City's distinctive character and identity. This study identifies elements and formulates recommendations for the RTBL of the T.B. Simatupang–Pinang Baris–Kampung Lalang Intersection corridor in Medan Sunggal District, utilizing an approach based on Hamid Shirvani’s urban design theories. The research identifies eight urban design elements and provides recommendations that can be incorporated into the Medan City RTBL document for this specific corridor area.